2014
DOI: 10.1016/j.ultsonch.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced OH radical generation by dual-frequency ultrasound with TiO2 nanoparticles: Its application to targeted sonodynamic therapy

Abstract: The present study demonstrated the enhanced hydroxyl (OH) radical generation by combined use of dual-frequency (0.5 MHz and 1 MHz) ultrasound (US) and titanium dioxide (TiO2) nanoparticles (NPs) as sonocatalyst. The OH radical generation became the maximum, when 0.5 MHz US was irradiated at an intensity of 0.8 W/cm(2) and 1 MHz US was irradiated at intensities at 0.4 W/cm(2) in the presence of TiO2 NPs under the examined conditions. After incorporation of TiO2 NPs modified with targeting protein pre-S1/S2, Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 37 publications
0
69
0
2
Order By: Relevance
“…SDT has attracted more interest as a promising therapy for the directed treatment of AS due to its minimal undesirable damage to surrounding normal tissues [28] and its deep penetration depth in tissues [8,9]. Our group found that low-intensity ultrasound induces little damage to tissue compared with high-intensity ultrasound [18,19,29].…”
Section: Discussionmentioning
confidence: 95%
“…SDT has attracted more interest as a promising therapy for the directed treatment of AS due to its minimal undesirable damage to surrounding normal tissues [28] and its deep penetration depth in tissues [8,9]. Our group found that low-intensity ultrasound induces little damage to tissue compared with high-intensity ultrasound [18,19,29].…”
Section: Discussionmentioning
confidence: 95%
“…More recently, several studies [91] highlighted the possibility to activate ROS formation through ultrasound irradiation. In this case the ROS production may be triggered by several mechanisms [111], as also schematized in Fig. 4 TiO 2 particles provide additional nuclei that increase the formation of ultrasound-induced cavitation bubbles.…”
Section: G Canavese Et Almentioning
confidence: 94%
“…Indeed, inertial cavitation phenomenon strongly depends on ultrasonic frequency, pressure amplitude, and, if pulsed ultrasound is used, on pulse repetition frequency and the number of cycles in each pulse [201]. In this regard, dual frequency ultrasound irradiation has also been recently proposed [111].…”
Section: Expert Opinion and Future Perspectivementioning
confidence: 99%
“…Fortunately, an alternative therapy exists: low-intensity ultrasound can penetrate deeply into tissues due to its much lower attenuation coefficient in tissues compared with lasers. [7][8][9][10][11] To resolve the problem of penetration depth, we made use of low-intensity ultrasound as a substitute for light in this study.…”
Section: Introductionmentioning
confidence: 99%